Vaginoplasty for Disorders of Sex Development - Marrocco, Giacinto A.; Guarino, Nino; Grammatico, Paola; Scommegna, Salvatore; Rapone, Anna Maria; Ungaro, Luciana; Morrone, Aldo (Frontiers in Endocrinology, 2013)
One of the most common problem found in patients with Disorders of Sexual Developments (DSD) is the absence or extreme hypoplasia of the vagina. The type of patients presenting this anomaly may belong to complete different groups: - patients with a urogenital sinus with urethra and vagina fusing together to form a common channel - patients with absent Müllerian structures and different degrees of external virilisation - complex malformations Treatment options: Treatment of these patients is under discussion and may consist, basically, in non-operative dilation methods or surgical creation of a neo-vagina. Consensus is far to be reached among the various surgical subspecialties regarding the optimal method of vaginal replacement. Adequate number of long term follow up patients are still non available so that most conclusions are based on small number series. The authors describe the different treatment options in detail.